Prequalified Connections Analysis for Moment Frames: Bolted Flange Plate (BFP) and Double-Tee Connection - Noek Sulandari; Anang Kristianto; Yosafat Aji Pranata (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
Design of steel structure connections is very important to realize the planned performance of the structures. SNI 7972:2020 specifies prequalified connections for steel moment frames for seismic applications. Bolted Flange Plate (BFP) and Double-Tee connections are non-patented bolt connections. The analysis of both types was carried out by also considering the provisions in SNI 7860:2020 and SNI 1729:2020 to obtain the advantages of each type for decision making purposes. BFP type produces a relatively smaller bolt diameter with more numbers. Attention must be paid to the length limit of the bolt group which does not exceed the depth of the beam. The need of connecting plates dimension is not difficult. Welding connection of plate to column must be carried out in the worlshop. Double-Tee connection analysis produces a larger bolt diameter with less amount. The thing that needs attention is the fulfillment of the Tee dimension which obtained from the cut hot-rolled profile.